Experience with treatment of fifty eight Iraqi patients with Acute Myeloid Leukemia - AL-Khalissi, Khudhair A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Adults with Acute Myelogenous Leukemia (AML) have the lowest survival rate of all leukemias. Complete remission (CR) rate after induction therapy is about 55-85%, however 30% of patients fail to achieve remission and they remain alive only for about a year. Consolidation chemotherapy results in 5-year overall survival (OS) of about 30%.Objectives: To study characteristics of adult patients with AML who attended Baghdad Teaching Hospital, their response to induction therapy and then to consolidation therapy, and their 5-year (OS) and disease free survival (DFS).Results: Eleven patients who received attenuated induction therapy had a median survival of 6-8 months and none of them achieved CR. Twenty six (55.5%) out of 47 patients who received 3+7 induction regimen had CR with treatment related mortality( TRM) of 34%, while OS and DFS were 30% and 34% respectively.Patients and methods: Sixty seven patients with AML (excluding M3) were admitted to the haematology ward /seventh floor/Medical city teaching hospital during 2008 with follow up till the end of 2012. Fifty eight patients included in the study, 47 patients (≤ 60-year) received 3+7 induction regimen. Nine (> 60 year) received attenuated courses of subcutaneous cytosar, or 2+5 regimen (according to presence or absence of co-morbidities). Those who attained CR were consolidated mainly with Modified MiDAC.Conclusion and recommendation: Early referral to the hospital is essential to avoid high early mortality. OS and DFS in our study is comparable to other studies in spite of shortage of antibiotics and cytotoxic therapy.